Pemberian kemoterapi pada tumor tulang primer - Benny dr; Nazar Moesbar (Fakultas Kedokteran USU, 2012)
Primary bone tumors are uncommon. The most common malignant tumor of bone is osteosarcoma, which accounts forapproximately 20 to 45% of all bone tumors followed by chondrosarcoma and the ewing's/PNET family of tumors.Amputation had been the standard method of treatment for most bone sarcomas, but the 1980’s witnessed the developmentof limb-sparing surgery for most malignant bone tumors. Today, limb-sparing surgery is considered safe and routine forapproximately 90% of patients with extremity osteosarcomas. Advances in orthopedics, bioengineering, radiographic imaging,radiotherapy, and chemotherapy have contributed to safer, more reliable surgical procedures. Paralleling these advances hasbeen the demonstrated effectiveness of adjuvant chemotherapy in dramatically increasing overall survival the bleak 15% to20% survival rate associated with surgery alone before the 1970’s rose to 55% to 80% with various adjuvant treatment regimensby the 1980’s.While therapy for patients with relapsed osteosarcoma often depends upon whether the disease is resectable, what priorchemotherapy a patient has received and the time to relapse, attention has begun to shift to a variety of novel therapeuticagents. Categories of these novel therapies include agents targeting receptor tyrosine kinases (RTKs), agents targeting signaltransductionpathways, agents that interfere with the tumor microenvironment, immunomodulatory agents and agents designedto overcome mechanisms of resistance.Keywords: osteosarcoma; chondrosarcoma; ewing’s sarcoma; chemotherapy